2018
DOI: 10.1136/archdischild-2017-314211
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in young people with congenital heart disease is better than expected

Abstract: The high HRQoL in young patients with CHD suggests that they can cope well with their disease burden. This holds true for all severity classes and diagnostic subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
(69 reference statements)
3
42
2
Order By: Relevance
“…A recent study carried out in relation to 1248 children, aged 7-17, compared the self-assessed general QoL using KINDL-R in 514 children with congenital heart disease and 734 healthy ones. The QoL results were higher than those obtained in our study: 78.6 ± 9.8 for children with heart problems, and 75.6 ± 10.1 for healthy ones [14]. KINDL-R was also used to assess the QoL of younger children than those participating in our study -Villalonga-Olives et al showed the following average results of KINDL-R on the basis of a group of 317 preschoolers: 67.88 ± 17.3 for boys, and 71.70 ± 16.37 for girls [15].…”
Section: Discussioncontrasting
confidence: 95%
“…A recent study carried out in relation to 1248 children, aged 7-17, compared the self-assessed general QoL using KINDL-R in 514 children with congenital heart disease and 734 healthy ones. The QoL results were higher than those obtained in our study: 78.6 ± 9.8 for children with heart problems, and 75.6 ± 10.1 for healthy ones [14]. KINDL-R was also used to assess the QoL of younger children than those participating in our study -Villalonga-Olives et al showed the following average results of KINDL-R on the basis of a group of 317 preschoolers: 67.88 ± 17.3 for boys, and 71.70 ± 16.37 for girls [15].…”
Section: Discussioncontrasting
confidence: 95%
“…A recent systematic review and meta-analysis showed that this was also true for older adult patients (mean age = 61 years old) with coronary heart disease (Le et al, 2018 ). This may not be the case for younger congenital heart disease patients (7–17 years old) who had QoL levels identical to those of healthy controls (Reiner et al, 2019 ). However, in the context of implantable cardioverter defibrillators (ICD), younger patients were found to cope with a lower QoL than older patients (Friedmann et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…No statistical significant association was observed between age and satisfaction with life in the current study. Reiner et al declared that young patients with CHD reported their health-related quality of life as high as their healthy peers (23).…”
Section: Discussionmentioning
confidence: 99%